Professional calling among nursing students: a latent profile analysis - Hu Jiang; Yongxia Mei; Xiaoxuan Wang; Zhixin Zhao; Beilei Lin; Wenna Wang; Zhenxiang Zhang (BMC, 2023)
Abstract Background One factor that influences nursing students' decision to pursue a nursing career is professional calling. It is important to comprehend nursing students' professional calling, which may have an impact on their career choice and career development. Objectives To investigate possible calling types and contributing variables among nursing students. Design Cross-sectional descriptive study. Participants A total of 10,583 nursing students were enrolled in this survey. Methods From November 16th, 2022, to January 17th, 2023, a cross-sectional study was carried out among nursing students using a convenient sampling. The subjects were given the Chinese Calling Scale and the General Demographic Information Questionnaire. Latent profile analysis (LPA) was used to separate nursing students' professional calling into a variety of subgroups. To find the variables connected to the prospective calling categories, we used ordinal and multinomial Logistic regression analysis. Results Respondents were divided into three calling groups, low (N = 3204), moderate (N = 4492), and high calling group (N = 2887), which accounted for 30.3%, 42.4%, and 27.3% of the total respondents, respectively, in accordance with the findings of the latent profile analysis. Across scale scores and dimensions for the three separate categories, three groups demonstrated statistically significant differences (both p < 0.001). Profile membership was predicted by 8 factors such as age, gender, location of origin, first volunteer experience, highest degree earned, marital status, student leadership experience, and political appearance. Conclusion Three latent calling patterns were found, and there was calling variability across nursing students. Special care should be given to students with low calling. Nursing students must use professional education tools to help them develop their career calling and stabilize the nursing team.